Dukungan Keluarga Dengan Manajemen Diri Diabetes Pada Pasien Diabetes Melitus Tipe 2: Tinjauan Sistematik - Safaruddin Safaruddin; Henny Permatasari (Jurnal Kesehatan Komunitas, 2022)
Diabetes mellitus (DM) is a chronic disease in the form of metabolic disorders characterized by blood sugar levels increase more than the normal threshold and is the top 10 cause of death globally. Ongoing DM care requires effective self-management education and support for patients and family members. The objective is to review family support interventions as a basic concept to improve people's self-management of diabetes. Using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method from three databases, PubMed, Google Scholar, and Scopus were reviewed for relevant articles. Results found that overall, family support had a positive impact on a healthy diet, increased perceived support, higher self-efficacy, improved psychological well-being, and better glycemic control. This systematic review found evidence that DSME with family support improves self-management behaviors and health outcomes among uncontrolled glycemic T2D patients. It is concluded demonstrating a DSME model that includes family involvement could be a useful direction for improving diabetes care.